Reasoning about equilibria in game-like concurrent systems - Gutierrez, J; Harrenstein, P; Wooldridge, M (Elsevier, 2016)
In this paper we study techniques for reasoning about game-like concurrent systems, where the components of the system act rationally and strategically in pursuit of logically-specified goals. Specifically, we start by presenting a computational model for such concurrent systems, and investigate its computational, mathematical, and game-theoretic properties. We then define and investigate a branching-time temporal logic for reasoning about the equilibrium properties of game-like concurrent systems. The key operator in this temporal logic is a novel path quantifier [NE]ϕ, which asserts that ϕ holds on all Nash equilibrium computations of the system.